THE CHARACTERISTIC OF PHYSICAL FITNESS OF SCHOOL STUDENTS OF 13-15 YEARS PLAYING VOLLEYBALL - Solyukov, A.A.; Egorova, A.M.; Bekmukhambetova, L.S. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2017)
This article presents the analysis of the research of physical preparedness of schoolchildren 13-15 years in volleyball. The article argues that achieving the optimal level of physical fitness contribute to various sports. Volleyball in this regard is a very attractive because the lessons can be held both indoors and outdoors. Minimal requirements to the technical equipment of the Playground.
Keywords: volleyball; physical fitness; training process